Empowerment of Surabi Laippung MSMEs through the Educreative Program as an Effort to Enhance Local Business Competitiveness - Muhammad Yusuf; Dwi Nabila Azzahra; A. Muh Naufal Anugrah; Taslim Taslim; Zulkarnain Zulkarnain (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
Micro and small businesses play an important role in local economic development, but still face challenges in improving business competitiveness, especially in traditional culinary MSMEs. This article aims to describe the implementation of the Educreative Program as an effort to empower Surabi Laippung MSMEs in the city of Makassar. This community service activity uses a Participatory Action Research (PAR) approach with stages of observation, participatory discussion, and implementation of cart design. The results of the activity show that improvements in cart design can enhance visual appearance, strengthen business identity, and increase the confidence of partners in running their businesses. The Educreative Program contributes positively to improving the image and competitiveness of traditional culinary MSMEs based on local wisdom.